SAUCE FILLER MACHINE AUTOMATIC SCREW SYSTEM EQUIPPED WITH ELECTRICAL CONTROL UNIT - Syah, Syeihan Syahrul; Maulana, Muhammad Irfan; Ainurroji, Adly Fitria; Ardiansyah, Mohammad Rizqi; Reynaldi, Alfian (International Journal of Tourism and Hospitality in Asia Pasific, 2018)
The purpose of this research to provide solutions existing problems in Sambal Goreng entrepreneur, especially on the process of sauce filling which is still using the traditional way. This research was comitted by designing an automatic filling machine, with a filler mechanism using a screw-driven piston technology, where the thread is rotated by an electric motor integrated with the timer. The result expected of prototype automatic filler machine is 1.2 kg/min flow rate, for the 150 g of sauce capacity storage takes 7.5 second . This machine is equipped with an easy charging method that is operated using only 1 button. the productivity of performance machine has been increased twice.